PENGARUH PENERAPAN PUNISHMENT TERHADAP AKHLAK SANTRI PUTRA DI PONDOK PESANTREN AL URWATUL WUTSQO BULUREJO DIWEK JOMBANG (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2020)
The application of Punishment in an institution is helpful in fostering the morals of students, because they will get sanctions that is being punished. This study discussed influence of punishment towards student’s morals of al Urwatul Wutsqo Boarding School of Bulurejo Diwek Jombang. The results stated that the application of punishment was good with 72% of 51 male students, and the morals of students showed a very good category with 69% of 51 male students. There is a strong and significant influence between Punishment and the Morals of students at the al Urwatul Wutsqo Boarding School Bulurejo Diwek Jombang. This is evident from results and obtained that was a high correlation about 0.944.